Enzymatic activities of non-starter lactic acid bacteria isolated from a traditional Portuguese cheese - Tavaria, Freni K. (2011)
Four strains of lactic acid bacteria, previously isolated from traditional Serra da Estrela cheese and duly identified as Lactobacillus paracasei ssp. paracasei, Leuconostoc mesenteroides ssp. dextranicum, Lactococcus lactis ssp. lactis and Enterococcus faecium, were tested for their aminotransferase, oxidase and dehydrogenase activities towards five amino acids in free form: two branched-chain (leucine and valine), one sulfur-containing (methionine) and two aromatic (phenylalanine and tryptophan) amino acids. For this purpose, both resting cells (RC) and crude cell-free extracts (CFE) were considered; their lyase and demethiolase activities (towards methionine and -keto- -methiolbutyric acid (KMBA), respectively) were also evaluated. Aminotransferase activity (AT) of RC was ca. 10-fold higher towards Met than towards Leu or Val. No AT activity was found in CFE, although these extracts displayed high dehydrogenase activity (DA) towards Phe, especially L. lactis ssp. lactis and E. faecium. In the case of L. paracasei ssp. paracasei and L. mesenteroides ssp. dextranicum, they showed high DA activity, which was ca. 10-fold higher towards Met than towards Leu or Val. E. faecium displayed high oxidase activity towards Met, and produced nine-fold more methanethiol from Met and five-fold more methanethiol from KMBA than the other three isolates under study.